Writing to Celebrate Happiness - Purwandari, Eny; Arifah, Handayani; Yeni, Mulati; Siti Nur, Hasanah; Nisa, Kamalia; Arini, Yuanto (Abdi Psikonomi, 2025)
Happiness is a goal for every individual, achieved through various means. Although the standardsand forms of happiness vary from person to person, happiness is an indicator of mental health. Achieving happiness can be achieved by fulfilling physical needs, but it is also important to fulfill non-physical needs to balance body and mind. The urgency of this research is that writing is one solution offered in efforts to address deteriorating mental health. Writing has been proven to be an effective means of controlling and managing stress (coping with stress). This writing activity will have an even more positive impact when done in ways that bring joy. This community service activity took the form of a writing seminar with the theme “Writing to Celebrate Happiness.” In general, the goal of this research was to provide understanding and scientific insight to the target group (students and university students) so they can cope with stress by writing about their emotional experiences. Specifically, the goal was to equip students and university students with the knowledge to overcome stress through writing about joyous experiences.